2006
DOI: 10.1002/ajp.20283
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic nephropathy in slender lorises (Loris lydekkerianus)

Abstract: In a colony of slender lorises, 20 deaths that occurred over a period of 11 years were investigated postmortem. Juvenile/adult polycystic nephropathy was observed in one newborn and 13 adult slender lorises. Although polycystic kidney disease (PKD) in humans and other animals is known to be inherited, it is not clear whether kidney alterations in slender lorises are genetically transmitted, stress related, or induced by microbiological influences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…One method of addressing buildup of plaque and tarter is to provide harder foods, like some insects; however, these foods may also create dental problems. Hard spikes on limbs of insects commonly fed to slender lorises in captivity, such as locusts and crickets, can damage the mucosa and introduce potentially pathogenic bacteria (Plesker & Schulze, , ). Dental abscesses were also common in these species, and trauma from spiky food is a potential cause of these issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method of addressing buildup of plaque and tarter is to provide harder foods, like some insects; however, these foods may also create dental problems. Hard spikes on limbs of insects commonly fed to slender lorises in captivity, such as locusts and crickets, can damage the mucosa and introduce potentially pathogenic bacteria (Plesker & Schulze, , ). Dental abscesses were also common in these species, and trauma from spiky food is a potential cause of these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Fuller et al () found that renal disease was a prevalent cause of death in lorises and pottos. Plesker and Schulze () reported polycystic nephropathy discovered on necropsy in a colony of slender lorises that had no clinical signs of renal disease. Alterations in kidney function and EPO production could explain erythrocyte abnormalities not observed clinically.…”
Section: Discussionmentioning
confidence: 99%
“…A review of necropsies of Loris tardigradus housed at a German university revealed several cases of cholelithiosis or gallstones, all of which were composed of cholesterol and were speculated to be related to dietary factors like the presence of egg yolk and the reduced insect composition in the captive diet (Plesker & Schulze 2006). Of the 2 cases of gallstones in the present study, 1 occurred in L. t. tardigradus and 1 in L. t. nordicus, but none were reported for slow lorises or pottos.…”
Section: Discussionmentioning
confidence: 99%
“…22 Polycystic kidney disease (PKD) is one of the most common genetic diseases in humans 10 and has frequently been reported in a variety of domestic, laboratory, and nondomestic species. 7,9,13,14,20 In humans, the diagnosis of PKD is reached when at least three cysts distributed between both kidneys are identified. 5 In domestic animals, most cases are considered to be congenital, and there is some evidence that the condition is heritable, with increased frequency in certain families of cats (Persian cats), dogs (Cairn terriers), pigs, and monkeys.…”
Section: Introductionmentioning
confidence: 99%